Evolutionary history and current distribution of the West Mediterranean lineage of Brucella melitensis in Italy. Issue 11 (8th November 2020) - Janowicz, Anna; De Massis, Fabrizio; Zilli, Katiuscia; Ancora, Massimo; Tittarelli, Manuela; Sacchini, Flavio; Di Giannatale, Elisabetta; Sahl, Jason W.; Foster, Jeffrey T.; Garofolo, Giuliano
Abstract : Ovine and caprine brucellosis, caused by Brucella melitensis, is one of the world's most widespread zoonoses and is a major cause of economic losses in domestic ruminant production. In Italy, the disease remains endemic in several southern provinces, despite an ongoing brucellosis eradication programme. In this study, we used whole-genome sequencing to detail the genetic diversity of circulating strains, and to examine the origins of the predominant sub-lineages of B. melitensis in Italy. We reconstructed a global phylogeny of B. melitensis, strengthened by 339 new whole-genome sequences, from Italian isolates collected from 2011 to 2018 as part of a national livestock surveillance programme. All Italian strains belonged to the West Mediterranean lineage, which further divided into two major clades that diverged roughly between the 5th and 7th centuries. We observed that Sicily serves as a brucellosis burden hotspot, giving rise to several distinct sub-lineages. More than 20 putative outbreak clusters of ovine and caprine brucellosis were identified, several of which persisted over the 8 year survey period despite an aggressive brucellosis eradication campaign. While the outbreaks in Central and Northern Italy were generally associated with introductions of single clones of B. melitensis and their subsequent dissemination within neighbouring territories, we observed weak geographical segregation of genotypes in the southern regions. Biovar determination, recommended in routine analysis of all Brucella strains by the World Organisation for Animal Health (OIE), could not discriminate among the four main global clades. This demonstrates a need for updating the guidelines used for monitoring B. melitensis transmission and spread, both at the national and international level, and to include whole-genome-based typing as the principal method for identification and tracing of brucellosis outbreaks.